4th International Conference on Intelligent Environments (IE 08) 2008
DOI: 10.1049/cp:20081141
|View full text |Cite
|
Sign up to set email alerts
|

YA-SRAP: yet another serverless RFID authentication protocol

Abstract: Several threats in RFID systems are obstacles to intermingle this technology into human lives. On the other hand ensuring flexible privacy mechanism has been an enormous challenge due to extremely inadequate computational storage of typical RFID tags. So in order to relieve tags from responsibility, privacy protection and security assurance was guaranteed by central server. In this paper, we describe serverless, lightweight, forward secured and untraceable authentication protocol for RFID tags. This authentica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Besides, they created a contact list which has been used in subsequent works. In 2008, some excellent protocols were presented by Ahamed et al Some researchers put forward a server-less searching protocol and a server-less authentication protocol separately [1,2]. These researches indicated that RFID security protocols without servers would be very meaningful for the development of RFID system [4].…”
Section: Related Workmentioning
confidence: 99%
“…Besides, they created a contact list which has been used in subsequent works. In 2008, some excellent protocols were presented by Ahamed et al Some researchers put forward a server-less searching protocol and a server-less authentication protocol separately [1,2]. These researches indicated that RFID security protocols without servers would be very meaningful for the development of RFID system [4].…”
Section: Related Workmentioning
confidence: 99%
“…In paper [1], authors proposed two serverless, lightweight authentication protocols, in which, authentication protocol 2 (denoted by "AP2") is secured against all major attacks. In protocol 2, a tag will release its data only to an authenticated reader and reader can only access its authorized tags.…”
Section: Related Workmentioning
confidence: 99%
“…The shared information contains the used for a tag along with the tag ID and reader ID of the reader which locates the particular tag within its cell. There is subtle difference between this shared information and ownership information of a reader [1]. From now on we refer to the shared information as Ownership Information in this context.…”
Section: 142mentioning
confidence: 99%
“…Radio frequency identification authentication is a basic method to guarantee security and privacy for an RFID system. If a tag is identified without being authenticated, attackers will be feasible to forge the tag's messages or to replay previous messages, pretending that the tagged object (e.g., an identification smartcard) is present.…”
Section: Introductionmentioning
confidence: 99%